Representasi Kekerasan Pada Serial Animasi Orb: On The Movements Of The Earth (Analisis Semiotika Roland Barthes) - Prakoso, Rizki Bayu; Syarief, Fauzi; Setyawan, Andi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to interpret and analyze the violent scenes in the animated series Orb: On The Movements Of The Earth using Roland Barthes' semiotic analysis. With a qualitative method and using a semiotic approach to interpret the signs and symbols contained in the violent scenes in this series. The analysis was carried out using Roland Barthes' semiotic concepts, namely denotation, connotation and myth to reveal the meaning of the violent scenes in the animated series. The results of this study found that there were scenes of verbal violence such as forcing, threatening and intimidating. Then there is also non-verbal violence, namely torturing, hitting, and strangling. In general, the violent scenes occurred as a result of studying a theory that was prohibited by the rules and belief doctrines of the authorities.